Reconciling community land and state forest claims in Indonesia: A case study of the Land Tenure Settlement Reconciliation Program in South Sumatra - Salim, M. Nazir; Wulan, Diah Retno; Pinuji, Sukmo (Forest and Society, 2021)
Longstanding land tenure claims in state forest by communities continues to pose a challenge to government institutions in Indonesia. Such conditions require institutions to develop mechanisms to assure communities of their rights in the state ideals of manifest justice and welfare. One government policy to reconcile these goals is the mechanism on Land Tenure Settlement Reconciliation in State Forests (Penyelesaian Penguasaan Tanah dalam Kawasan Hutan/PPTKH). This study aims to describe this policy in the context of fieldwork experience related to fundamental problems in the process of identification and settlement of land tenure claimed by communities in state forests. Data collection was obtained through participant observation conducted with communities in Ogan Kemoring Ulu Regency by identifying and verifying community lands in state forests. This method allowed for a more nuanced understanding of settlement challenges and afforded the opportunity to develop a formula for addressing conflicts. The results of the study show that the main problems are a lack of access to information related to the PPTKH policy emergent from ineffective dissemination of information combined with an underdeveloped capacity of processes that support the community to convene and discuss with government actors, academics/researchers, and activists/scholars. The participative learning process conducted by the authors helped the community effectively prepare documents to propose to an Inventory and Verification (Inver) team of Land Tenure in State Forests. Therefore, going forward more collaborative work is needed within the framework of community assistance and capacity building so that the communities have the means and resources to able to understand the challenges of land tenure recognition and be empowered to propose such mechanisms independently. Communities who claim land in state forests depend upon formalized legality, without which can potentially harm their access and assets.